1999
DOI: 10.2337/diabetes.48.3.664
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber type-specific defects in insulin signal transduction to glucose transport in diabetic GK rats.

Abstract: To determine whether defects in the insulin signal transduction pathway to glucose transport occur in a muscle fiber type-specific manner, post-receptor insulin-signaling events were assessed in oxidative (soleus) and glycolytic (extensor digitorum longus [EDL]) skeletal muscle from Wistar or diabetic GK rats. In soleus muscle from GK rats, maximal insulin-stimulated (120 nmol/l) glucose transport was significantly decreased, compared with that of Wistar rats. In EDL muscle from GK rats, maximal insulin-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 30 publications
8
56
1
3
Order By: Relevance
“…In vivo in all tissues, insulin action on Akt isoforms is better preserved than insulin action on PI3K, and in some tissues, activity of Akt1 or Akt2 is even increased. Similar discrepancies in PI3K and Akt activities have recently been reported with insulin infusion in obese humans with type 2 diabetes (20) and in several insulin-resistant models in rats (39,40,42). These findings suggest the presence of either PI3K-independent pathways that regulate Akt activity in insulin-resistant states or regulatory steps distal to the activation of PI3K.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In vivo in all tissues, insulin action on Akt isoforms is better preserved than insulin action on PI3K, and in some tissues, activity of Akt1 or Akt2 is even increased. Similar discrepancies in PI3K and Akt activities have recently been reported with insulin infusion in obese humans with type 2 diabetes (20) and in several insulin-resistant models in rats (39,40,42). These findings suggest the presence of either PI3K-independent pathways that regulate Akt activity in insulin-resistant states or regulatory steps distal to the activation of PI3K.…”
Section: Discussionsupporting
confidence: 84%
“…Unlike in adipocytes, in skeletal muscle of obese rats, insulin-stimulated activities of Akt1 and Akt2 are reduced 30%. This reduction is unlikely to impair insulin-stimulated glucose transport, since recent studies in models of insulin resistance induced with hyperglycemia in vivo (39) or in vitro (40) show that an ~40% reduction in insulin-stimulated Akt activation in skeletal muscle is associated with no defect in insulin-stimulated glucose transport. On the other hand, glucose metabolism to glycogen is impaired (40), potentially indicating differential dependency of glucose transport and glycogen synthesis on Akt activation.…”
Section: A B Cmentioning
confidence: 97%
See 1 more Smart Citation
“…Severe pathophysiological symptoms including defects in insulin secretion and peripheral insulin resistance usually occur by 4 weeks of age (Abdel-Halim et al, 1994;Portha et al, 1991). GK skeletal muscles appear to exhibit a reduced percentage of oxidative fibres (Yasuda et al, 2002) and also show fibre type-specific defects, with IRS1 and PI3K activity decreased primarily in oxidative muscles (Song et al, 1999). Activities of insulin signalling intermediates including PI3K, PKB/Akt and ERK were found to be impaired in GK muscle (Steiler et al, 2003;Krook et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several independent lines of evidence have shown that decreased insulin-dependent Akt phosphorylation is associated with a variety of insulin-resistant states (33)(34)(35)(36), and interventions that increase the level of Akt phosphorylation in muscle cells and other tissues lead to increased insulin-stimulated glucose transport (35,36). An interesting feature of the effect of rexinoids on Akt phosphorylation is that it was similar in both the slow-twitch soleus muscle as well as in muscle such as EDL that is primarily composed of fast-twitch myofibers.…”
Section: Discussionmentioning
confidence: 99%